Cisco CCT routing and switching (100-490) - Wong, Ronnie; Bryan, Wes (Packt Publishing, 2024)
The course begins by laying the foundation of basic networking hardware, introducing you to pivotal networking models, and navigating through Layer 1 and 2 technologies. You will grasp the core responsibilities in networking, delve into network addressing, and learn to use basic network utilities efficiently. The course focuses on deepening your understanding of Cisco equipment and components, including detailed insights into Cisco port characteristics and memory functions. You'll gain hands-on experience in installing, operating, and troubleshooting Cisco devices, accessing the Cisco IOS, and mastering fundamental Cisco IOS commands. The course wraps up by teaching you advanced skills like upgrading Cisco IOS on routers, password recovery techniques, performing factory resets, and utilizing additional tools for comprehensive network management. Each step is designed to strengthen your proficiency in Cisco's cutting-edge routing and switching technologies. What you will learn Identify key networking hardware components Understand essential networking models Utilize basic Cisco IOS commands effectively Perform network troubleshooting using Windows Execute password recovery on Cisco routers Conduct factory resets on Cisco switches Audience This course is ideal for IT professionals, network engineers, and tech enthusiasts seeking to enhance their skills in Cisco routing and switching. This course is perfect for those aspiring to gain Cisco CCT Routing and Switching certification. About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Ronnie Wong: Ronnie Wong has had a diverse career, from diesel service and ministry to computer repair and network administration in small businesses. He set up networks and servers and created policies in these roles. As an Edutainer at ITProTV, now ACI Learning, he started as an IT technical instructor, later working as a contract trainer for the University of Florida, Marion County School Systems, and Nationwide Insurance. He provided Cisco, Microsoft Windows, CompTIA, and IT security training to military and DoD personnel. Now the Director of Content Development at ACI Learning, Ronnie's credentials include CCNP Enterprise Infrastructure, CCNA, CompTIA's A+, Network+, Security+, ISC2 CC, CNA Security, and PCNSA. Wes Bryan: Wes Bryan embarked on his IT career path in 2009, initially as a mentored learning instructor, and later transitioning into a technical IT instructor. His exceptional teaching skills were recognized with three global teaching awards for 'Global Technical Instructor' during his early teaching years. Wes has made notable contributions as a member of the CIN (CompTIA Instructor Network) Advisory Board and the Board of Directors for CompTIA AITP (Association of Information Technology Professionals). Certifications: CompTIA A+, Network+, Security+, Server+, Cloud+, CySA+; MCSA; MTA; MCTS; MCP; MS; MCT.
Online resource; title from title details screen (O'Reilly, viewed January 23, 2024)
Keywords: Computer networks -- Study guides -- Examinations; Routing (Computer network management) -- Study guides -- Examinations; Internetworking (Telecommunication) -- Study guides -- Examinations; Réseaux d'ordinateurs; Examens; Guides de l'étudiant; Routage (Gestion des réseaux d'ordinateurs); Examens; Guides de l'étudiant; Interconnexion de réseaux (Télécommunications); Examens; Guides de l'étudiant; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet